Implementasi Prinsip Business Judgment Rule Dalam Perlindungan Hukum Direksi BUMN - Muhammad, Ogan (Universitas Jayabaya, 2025)
This research examines the implementation of the Business Judgment Rule (BJR) as a legal safeguard for directors of state-owned enterprises (BUMN) in Indonesia. Although normatively recognized under Article 97(5) of Law No. 40 of 2007 on Limited Liability Companies and reinforced by Government Regulation No. 23 of 2022, its application remains hindered by legal dualism and judicial inconsistency. Through a normative juridical approach, the study finds that the broad interpretation of “state financial losses” under the Anti-Corruption Law obscures the distinction between business risks and unlawful acts. To ensure legal certainty and corporate accountability, the study recommends harmonizing corporate and public law, issuing judicial guidelines by the Supreme Court, and strengthening Good Corporate Governance (GCG) practices within state-owned enterprises